Induction of Day-Time Periodic Breathing is Associated With Augmented Reflex Response From Peripheral Chemoreceptors in Male Patients With Systolic Heart Failure - Niewinski, Piotr; Tubek, Stanislaw; Paleczny, Bartlomiej; Banasiak, Waldemar; Ponikowski, Piotr (Frontiers in Physiology, 2022)
Spontaneous day-time periodic breathing (sPB) constitutes a common phenomenon in systolic heart failure (HF). However, it is unclear whether PB during wakefulness could be easily induced and what are the physiological and clinical correlates of patients with HF in whom PB induction is possible. Fifty male HF patients (age 60.8 ± 9.8 years, left ventricle ejection fraction 28.0 ± 7.4%) were prospectively screened and 46 enrolled. After exclusion of patients with sPB the remaining underwent trial of PB induction using mild hypoxia (stepwise addition of nitrogen gas to breathing mixture) which resulted in identification of inducible (iPB) in 51%. All patients underwent assessment of hypoxic ventilatory response (HVR) using transient hypoxia and of hypercapnic ventilatory response (HCVR) employing Read’s rebreathing method. The induction trial did not result in any adverse events and minimal SpO2 during nitrogen administration was ~85%. The iPB group (vs. non-inducible PB group, nPB) was characterized by greater HVR (0.90 ± 0.47 vs. 0.50 ± 0.26 L/min/%; p<0.05) but comparable HCVR (0.88 ± 0.54 vs. 0.67 ± 0.68 L/min/mmHg; p=NS) and by worse clinical and neurohormonal profile. Mean SpO2 which induced first cycle of PB was 88.9 ± 3.7 %, while in sPB mean SpO2 preceding first spontaneous cycle of PB was 96.0 ± 2.5 %. There was a reverse relationship between HVR and the relative variation of SpO2 during induced PB (r=-0.49, p=0.04). In summary, PB induction is feasible and safe in HF population using simple and standardized protocol employing incremental, mild hypoxia. Pathophysiology of iPB differs from sPB, as it relies mostly on overactive peripheral chemoreceptors. At the same time enhanced HVR might play a protective role against profound hypoxia during iPB.